Fca´s merger chess: reassessing the decision for psa instead of Renault - Janßen, Christian (2024)
The case study examines the merger of equals between Fiat Chrysler Automobiles and Peugeot S.A., which created the world's third-largest automaker. It examines whether the merger was sensible for FCA, looking at strategic, valuation, and corporate governance dimensions. The analysis confirmed that the merger makes sense for FCA in every respect. The individual part reassesses FCA's choice of PSA over Renault, concluding that PSA was the better option.